Ответ: [tex]4^{10}+1[/tex]
Объяснение:
[tex]\dfrac{4^{19} + 4^{18} + \ldots + 4 + 1}{4^9 + 4^8 + \ldots + 4 + 1}=4^{10}+1[/tex]
Формула для нахождения суммы первых членов геометрической прогрессии :
[tex]\sf S_n = \dfrac{b_1(q^n-1)}{q-1}[/tex]
В числителе
[tex]S_{20}= \dfrac{1(4^{20}-1)}{4 -1} = \dfrac{4^{20}-1}{3}[/tex]
В знаменателе
[tex]S_{10}= \dfrac{1(4^{10}-1)}{4 -1} = \dfrac{4^{10}-1}{3}[/tex]
Тогда :
[tex]\dfrac{4^{19} + 4^{18} + \ldots + 4 + 1}{4^9 + 4^8 + \ldots + 4 + 1} =\dfrac{\dfrac{4^{20}-1 }{3} }{\dfrac{4^{10}-1}{3} } =\dfrac{(4^{10}-1)(4^{10}+1)}{4^{10}-1} = 4^{10}+1[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: [tex]4^{10}+1[/tex]
Объяснение:
[tex]\dfrac{4^{19} + 4^{18} + \ldots + 4 + 1}{4^9 + 4^8 + \ldots + 4 + 1}=4^{10}+1[/tex]
Формула для нахождения суммы первых членов геометрической прогрессии :
[tex]\sf S_n = \dfrac{b_1(q^n-1)}{q-1}[/tex]
В числителе
[tex]S_{20}= \dfrac{1(4^{20}-1)}{4 -1} = \dfrac{4^{20}-1}{3}[/tex]
В знаменателе
[tex]S_{10}= \dfrac{1(4^{10}-1)}{4 -1} = \dfrac{4^{10}-1}{3}[/tex]
Тогда :
[tex]\dfrac{4^{19} + 4^{18} + \ldots + 4 + 1}{4^9 + 4^8 + \ldots + 4 + 1} =\dfrac{\dfrac{4^{20}-1 }{3} }{\dfrac{4^{10}-1}{3} } =\dfrac{(4^{10}-1)(4^{10}+1)}{4^{10}-1} = 4^{10}+1[/tex]